Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae) - Bakkes, Deon K.; Sole, Catherine L.; Mansell, Mervyn W. (Zootaxa, 2017)
Afrotropical Psychopsidae Handlirsch are revised based on morphology. Molecular data from a previous study enables updated taxonomy in this revision, and morphology corroborates phylogenetic divergences. The genus Silveira was found to form a lineage separate from Zygophlebiinae based on molecular data and six morphological synapomorphies. In this revision, Silveira is moved to a new subfamily, leaving only Cabralis and Zygophlebius in Zygophlebiinae. Two new species of Cabralis are described. Afrotropical Psychopsidae now comprise ten species, three genera and two subfamilies. A dichotomous key to these taxa is provided, along with a web link to a fully-illustrated and interactive multi-access LUCID v3 key. High resolution images and distribution maps are provided for all species.